Limiter observations during W7-X first plasmas. (3rd April 2017) - Wurden, G.A.; Biedermann, C.; Effenberg, F.; Jakubowski, M.; Niemann, H.; Stephey, L.; Bozhenkov, S.; Brezinsek, S.; Fellinger, J.; Cannas, B.; Pisano, F.; Marsen, S.; et al.
Abstract: During the first operational phase (referred to as OP1.1) of the new Wendelstein 7-X (W7-X) stellarator, five poloidal graphite limiters were mounted on the inboard side of the vacuum vessel, one in each of the five toroidal modules which form the W7-X vacuum vessel. Each limiter consisted of nine specially shaped graphite tiles, designed to conform to the last closed field line geometry in the bean-shaped section of the standard OP1.1 magnetic field configuration (Sunn Pedersen et al 2015 Nucl. Fusion 55 126001). We observed the limiters with multiple infrared and visible camera systems, as well as filtered photomultipliers. Power loads are calculated from infrared (IR) temperature measurements using THEODOR, and heating patterns (dual stripes) compare well with field line mapping and EMC3-EIRENE predictions. While the poloidal symmetry of the heat loads was excellent, the toroidal heating pattern showed up to a factor of 2×  variation, with peak heat loads on Limiter 1. The total power intercepted by the limiters was up to ~60% of the input ECRH heating power. Calorimetry using bulk tile heating (measured via post-shot IR thermography) on Limiter 3 showed a difference between short high power discharges, and longer lower power ones, with regards to the fraction of energy deposited on the limiters. Finally, fast heating transients, with frequency  >1 kHz were detected, and their visibility was enhanced by the presence of surface coatings which developed on the limiters by the end of the campaign.